Neuronal changes during forebrain evolution in amniotes: an evolutionary developmental perspective. - Molnár, Z; Butler, AB (2002)
Embryology is the interface of genetic inheritance and phenotypic expression in adult forms, and as such is uniquely positioned to illuminate both. Embryonic cell migration pattern, transient connectivity, axonal growth kinetics and fasciculation patterns can clearly be substantially impacted at the striatocortical junction, which appears to be critical for telencephalic development. Similarly, the big questions concerning pallial evolution in amniotes all involve the pivotal region at the pallial-subpallial boundary, an area where complex developmental cross-currents may be involved in the specification of multiple structures that are thus related to each other. We review some of the positions based on recent genetic data and/or hodology, then suggest that comparative studies of intervening, embryological events may resolve some of the apparent conflicts and illuminate the evolutionary scenario. We propose a new hypothesis, the collopallial field hypothesis, which specifies that the anterior dorsal ventricular ridge of sauropsids and a set of structures in mammals--the lateral neocortex, basolateral amygdalar complex, and claustrum-endopiriform nucleus formation--are homologous to each other as derivatives of a common embryonic field. We propose that in mammals the laterally lying collopallium splits, or differentiates, into deep (claustroamygdalar) and superficial (neocortical) components, whereas in sauropsids, this split does not occur.